Odpowiedzi

2009-12-05T17:01:46+01:00
X+x=10
x-y=0

2x=0
x-y=10

2x=0
-y=10-x / *2

2x=0
-2y=20-2x

2x=0
-2y=20-0

2x=0
-2y=20-0 / : (-2)
y=10
x=0

8x-6y=10
7x-y=5

8x-6y=10
-y=5-7x

8x-6y=10
y=-5+7x

8x-6(-5+7x)=10
y=-5+7x

8x+30 -42x=10
y=-5+7x

-34x=-20 34x=20 / :34 x=¹⁰/₁₇
x=10/17
y=-5+7(10/17)
x=10/17
y=-5+70/17
x=10/17
y=-85/17+70/17
x=10/17
y=-15/17

12p-7r=-16
p-3r=-69

12p-7r=-16
p=69+3r

12(69+3r)-7r=-16
p=69+3r

828+36r-7r=-16
p=69+3r

29r=-16-828
p=69+3r

29r=-846 r=-846/29
p=69+3(-846/29)

r=-846/29
p=2001/29+(-2538/29

r=-29 ⁵/₂₉
p= -537/29 p=-18 ¹⁵/₂₉



11k+17l=45
13k+l=15

11k+17l=45
l=15-13k

11k+17(15-13k)=45
l=15-13k

11k+255-221k=45
l=15-13k

210k=45-255 210k=-210 k= -1

k=-1
l=15-13(-1)
k=-1
l=15+13
k=-1
l=28

8a+9b=36
a-16b=210

8a+9b=36
a=210+16b

8(210+16b)+9b=36
a=210+16b

1680+128b+9b=36
a=210+16b

137b=36-1680
a=210+16b

137b=-1644 b= -12
a=210+16(-12)

b=-12
a=210-192

b=-12
a=18

6a-21b=228
a-12b=21

6a-21b=228
a=21-12b

6(21-12b)-21b=228
a=21-12b

126-72b=228
a=21-12b

-72b=228-126 -72b=102:(-72)
a=21-12b

b=-102/72
a=21-12(-102/72)

b=-102/72
a=1512/72+1224/72

b=-102/72
a=2736/72

b=- 1¹⁵/₃₆
a=38
1 4 1
Najlepsza Odpowiedź!
2009-12-05T17:13:45+01:00
A)x+x=0
x-y=10

2x=0/:2
x-y=10

x=0
0-y=10

x=0
-y=10/*(-1)

x=0
y=-10

b)8x-6y=10
7x+y=5/*6

8x-6y=10
42x+6y=30

50x=40/:50
x=0,8

8x-6y=10
x=0,8

8*0,8-6y=10
x=0,8

6,4-6y=10
x=0,8

-6y=10-6,4
x=0,8

-6y=3,6/:(-6)
x=0,8

y=-0,6
x=0,8

c)12p-7r=-16
p-3r=-69

12p-7r=-16
p=-69+3r

12(-69+3r)-7r=-16
p=-69+3r

-828+36r-7r=-16
p=-69+3r

29r=-16+828
p=-69+3r

29r=812/:29
p=-69+3r

r=28
p=-69+3r

r=28
p=-69+3*28

r=28
p=-69+84

r=28
p=15

d)11k+17l=45
13k+l=15

11k+17l=45
l=15-13k

11k+17(15-13k)=45
l=15-13k

11k+255-221k=45
l=15-13k

11k-221k=45-255
l=15-13k

-210k=-210/:(-210)
l=15-13k

k=1
l=15-13*1

k=1
l=15-13

k=1
l=2

e)8a+9b=36
a-16b=210/*(-8)

8a+9b=36
-8a+128b=-1680

137b=-1644/:137
b=-12

8a+9b=36
b=-12

8a+9*(-12)=36
b=-12

8a-108=36
b=-12

8a=36+108
b=-12

8a=144/:8
b=-12

a=18
b=-12




















1 5 1